Azoxystrobin sensitivity, morphological and genetic marker studies of Colletottrichum gloeosporioides (Penz) penz. and sacc. from mango and C. capsici (H. syd.) E. butl. and bisby from chilli - Quah, Ju Lee (2000)
This project evaluated the sensitivities of Collelotric gleasporioides and capsici towards the fungicide Azoxystrobin. This was complemented by morphological and genetic marker studies of the two species in order to record the natural variation of the two species. Twenty five cultures of C gloeosporioides were isolated from mangoes (Mangifera indica) and 22 of cultures of C. capsici isolated from chillies (Capsicum annum) were used. They were collected from Malaysia. Indonesia, Thailand, Philippines and Taiwan. Single spore cultures were made to establish the species identity. Isolates of both species were tested separately for fungicide sensitivity. The spore suspension was optimised to 10.5 spores/ml for bioassays.: :The assay medium used was a glycerol based Alkyl Ester broth, amended with rates of technical azoxystrobin at 0.0001, 0.001, 0.01 and 0.1 ppm with blanks of Alkyl Ester broth as controls. The tests were divided into statistical validation and actual baseline studies. For validation studies, 6 isolates in 6 replicate test!; were used in the calculation of experimental errors. The baseline test consisted of 3 rephcate treatments per Azoxystrobin mte per isolate with double controls for 14 isolates of C. gloeosporioides and 15 isolates of C. capsici. The validation isolates were included together with the baseline isolates during final analysis to give a total of20 isolate. for C. gloeosporioides and a total of21 isolates for C. capsici. The Alkyl Ester broth was inoculated with spore-suspensions of each isolate separately to give a final concentration of l0⁵ spores/ml in the mixture. 60 µl droplets of the broth-spore mixtures were incubated. in 55 mm petri dishes and covered with cover slips. The reference isolate PMLI was included in all tests to monitor the consistency. Assessment was done by scoring the number of spores out of 50 that showed germ tube elongation to a minimum of twice the spore length. Dose responses were plotted of log rate against the number of spores germinated to derive 80% effective dose or ED₈₀ values for each isolate. This entire experiment was repeated twice and the data analysed to determine the intra and inter experimental variation. Sensitivity values were also calculated by linear regression analysis using arcsine transformation of the data (ACSAPWIN). Results showed that the ED₈₀ range for C. gloeosporioides was between 0.01 ppm to 0.1 ppm white this was between 0.001 ppm to 0.01 ppm for C. capsici.